2019
DOI: 10.1088/1757-899x/532/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber length on the mechanical properties and water absorption of bamboo fiber/polystyrene-modified unsaturated polyester composites

Abstract: The paper presents the effect of fiber length on the mechanical properties and water absorption of bamboo fiber/polystyrene-modified unsaturated polyester composites. The fiber length varied from 2.5 mm to 15 mm at the fiber volume fraction of 0.2, 0.25 and 0.3. For water absorption, the specimens were immersed in distilled water at temperature of 40°C. The results showed that for all volume fractions, the tensile, flexural, and the impact properties tended to increase with the increase of fiber length; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…The samples consist mainly of alcohol, phenol, ester, ketone, and alkene, consistent with the composition of the main components of biomass: cellulose, hemicellulose, lignin, and pectin. [37,48] Interestingly, both pine and coconut flour exhibit strong absorption near 1050 cm À1 , consistent with C O stretching in a primary alcohol contained in cellulose. [37,49] However, after pyrolysis of pine and coconut flour, absorption near 1050 and 3400 cm À1 is reduced, suggesting that primary alcohol or ethanol was consumed or converted during pyrolysis.…”
Section: Chemical Characterizationmentioning
confidence: 79%
See 2 more Smart Citations
“…The samples consist mainly of alcohol, phenol, ester, ketone, and alkene, consistent with the composition of the main components of biomass: cellulose, hemicellulose, lignin, and pectin. [37,48] Interestingly, both pine and coconut flour exhibit strong absorption near 1050 cm À1 , consistent with C O stretching in a primary alcohol contained in cellulose. [37,49] However, after pyrolysis of pine and coconut flour, absorption near 1050 and 3400 cm À1 is reduced, suggesting that primary alcohol or ethanol was consumed or converted during pyrolysis.…”
Section: Chemical Characterizationmentioning
confidence: 79%
“…a Associated with C═O in pectin/ hemicelluloses. [48] b Associated with C O in lignin. [48] evaluating the potential for biocarbon to act as a reinforcing agent in PA6-glass hybrid composites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other lengths of fiber used for the study were 3, 5 and 7 mm. Sugiman et al (2019) investigated the effect of fiber length on the mechanical and water absorption properties of composite made of bamboo fiber/polystyrene-modified unsaturated polyester resin matrix. The range of fiber length used in the study was varied from 2.5 mm to 15 mm and fiber volume fraction at 0.2, 0.25 and 0.3.…”
Section: Modification Of Fiber Surface Characteristicsmentioning
confidence: 99%
“…Several factors affect the performance of the physical properties of CB, for example, various lengths of the fibre (Akasah et al, 2019). Research conducted by Sugiman et al (2019) found that the fibre length influenced the workability and increasing impact strength of cement board. Heterogeneous fibre length can improve various mechanical properties of CB as compared to only one larger fibre size.…”
Section: Introductionmentioning
confidence: 99%